Comparison of The Effectiveness of Remifentanyl versus Fentanyl in Pediatric Undergoing Methotrexate Therapy - Purwoko, Purwoko; Putro, Bambang Novianto; Pamungkas, Ferdy; Siswanto, Febby Gunawan (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Anesthesia procedure is routinely performed for some painful pediatric oncologic procedures such as lumbar puncture (LP) and bone marrow examination (BME). Several studies mentioned that fentanyl and remifentanyl are often used as anesthetic agent of this procedure, but none of them compare the recovery time of both agent. This study aims to compare the recovery time of fentanyl and remifentanyl in pediatric patients undergoing methoterexate therapy.Subjects and Method: This was a double-blind randomized controlled trial on 36 patients who underwent intratechal methotrexate chemoterapy under general anesthesia anesthesia in pediatric intervention room of Moewardi General Hospital Surakarta that met inclusion criteria. The dependent variable was recovery time and the independent variable were fentanyl and remifentanyl. The samples were divided into 2, Fentanyl (F) and Remifentanyl (R) group. Recovery time was recorded after the procedure until the subject reached Pediatric Glasgow Comma Scale (PGCS) of 15. Statistical analysis was Mann Whitney U Test using SPSS 25 for Windows.Results: The mean recovery time of F group was 373.39 ± 29.48 seconds, while R group was 124.67±11.55 seconds. There was a significant difference in recovery time between patients in the Fentanyl group and the Remifentanyl group (p= 0.000).Conclusion: Remifentanyl recovery time was significantly faster than with fentanyl in pediatric patients undergoing intrathecal methotrexate chemotherapy.Keywords: Fentanyl, Methotrexate, Outpatient anesthesia, Recovery time, RemifentanylCorrespondence: Ferdy Pamungkas. Anesthesiology Department, Moewardi General Hospital, Surakarta. Jalan Kolonel Sutarto 132 Jebres, Kecamatan Jebres, Surakarta City 57126. Central Java, Indonesia. dr.ferdypamungkas@gmail.com. +6281230269501.Indonesian Journal of Medicine (2022), 07(01): 115-121https://doi.org/10.26911/theijmed.2022.07.01.12